Examining the Levels of Distress Tolerance and Intolerance of Uncertainty for Women Receiving Infertility Treatment - Serter, Gulden Ozturk; Celik, Seher Balci (Cyprus Mental Health Inst, 2025)
During infertility treatment, prospective mothers are often confronted with negative experiences such as stress, distress, anxiety, depression, and uncertainty. It is believed that the ability to tolerate distress and endure the uncertainties caused by treatment plays a crucial role in achieving successful outcomes. Therefore, the aim of this study is to examine the levels of intolerance of uncertainty and distress tolerance in women undergoing infertility treatment. This is a cross-sectional, comparative study conducted through purposive sampling. A total of 287 women receiving infertility treatment participated in the study. The Intolerance of Uncertainty Scale and the Distress Tolerance Scale were used in data collection. The results of the study revealed that as age increases, the level of intolerance of uncertainty increases (p<0,001). Additionally, a significant difference was found between the women's level of education and their distress tolerance levels (p<0,05). The research also identified a low but statistically significant positive correlation between the Regulation subdimension of Distress Tolerance and the Prospective Anxiety subdimension of Intolerance of Uncertainty (p<0.05). Since infertility is a difficult, exhausting, stressful, and uncertain treatment process, couples and especially women experience a heightened sense of "uncertainty." Consequently, it can be concluded that as women age and are unable to experience motherhood, their intolerance toward the uncertain process increases with each treatment attempt.
Keywords: Infertility; Distress Tolerance; Intolerance of Uncertainty; Infertility; Distress Tolerance; Intolerance of Uncertainty; In Vitro Fertilization (IVF); Treatment